2021
DOI: 10.1002/em.22421
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals modulate DNA compaction and methylation at CpG sites in the metal hyperaccumulator Arabidopsis halleri

Abstract: Excess heavy metals affect plant physiology by inducing stress symptoms, however several species have evolved the ability to hyperaccumulate metals in above‐ground tissues without phytotoxic effects. In this study we assume that at subcellular level, different strategies were adopted by hyperaccumulator versus the non‐accumulator plant species to face the excess of heavy metals. At this purpose the comet assay was used to investigate the nucleoid structure modifications occurring in response to Zn and Cd treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 50 publications
(68 reference statements)
1
13
0
Order By: Relevance
“…In Hibiscus cannabinus , increased methylation was associated with increasing chromium levels (Ding et al 2016). In Arabidopsis halleri , cadmium treatments increased CpG methylation of genes responsible for symmetric methylation (Galati et al 2021). In rice, a model for nutrient stress, the expression of Heavy Metal Transporting ATPases (HMAs) was modified and retained over generations and modulated by the methylation of specific TEs (Cong et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In Hibiscus cannabinus , increased methylation was associated with increasing chromium levels (Ding et al 2016). In Arabidopsis halleri , cadmium treatments increased CpG methylation of genes responsible for symmetric methylation (Galati et al 2021). In rice, a model for nutrient stress, the expression of Heavy Metal Transporting ATPases (HMAs) was modified and retained over generations and modulated by the methylation of specific TEs (Cong et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the Ganges (GA) ecotype has shown superior Cd accumulation and hypertolerance when compared to other populations studied so far (Assuncão et al 2003). In a previous work, we used alkaline and methy-sens comet assays to show that the Cd hyperacculator and hypertolerant species Arabidopsis halleri, differently to the non-tolerant species Arabidopsis thaliana, condenses its nucleus by DNA methylation in response to Cd treatment, suggesting a role of DNA methylation for proper plant development (Galati et al 2021). In this work, we compared the Cd response in N. caerulescens GA vs the non-tolerant A. thaliana analyzing i) the possible DNA damages by alkaline comet assay; ii) the modulation of DNA methylation by methy-sens comet assay; iii) the superoxide dismutase (SOD) activity and ROS production, measuring the three oxidative stress biomarkers, H 2 O 2 , 7,8-Dihydro-8-oxo-2′-deoxyguanosine (8-oxo-dG) and superoxide anion; and iv) the expression of genes involved in symmetric and non-symmetric DNA methylation and genes coding for enzymes linked to oxidative stress response.…”
Section: Introductionmentioning
confidence: 94%
“…This assay enables to detect DNA damage even at low concentrations of contaminants (Rodriguez et al 2019) and allows the identification of modifications in the DNA that alters the supercoiling of the molecule, since loops move towards the anode during electrophoresis (Tice et al 2000). In a previous work, the comet assay was employed to compare the effects of Cd exposure on the integrity of leaf cell nuclei in the Cd hypertolerant and hypercaccumulator species Arabidopsis halleri PL22 vs the non-tolerant species A. thaliana, showing a highly condensed nucleus in the hyperacculator species upon Cd treatment and a nucleus degradation in the non-tolerant one (Galati et al 2021). A similar result was observed in the Ni hyperaccumulator N. caerulescens Monte Prinzera population vs the non-tolerant A. thaliana.…”
Section: Dna Damage Induced By CD On Leaf Nucleimentioning
confidence: 99%
See 1 more Smart Citation
“…So far, experimental evidence on the contribution of epigenetic mechanisms to plant heavy metal tolerance has shown that DNA methylation could have a direct protective role. For example, metal tolerant plants like Arabidopsis halleri -in response to Cd -and Noccaea caerulescens -in response to Ni showed hypermethylation of DNA and no heavy metal-induced DNA damage 34,35 . Non-tolerant species like the moss Physcomitrium patens , however, showed overall DNA hypomethylation and significant signs of DNA strand breaks in response to Mn 36 .…”
Section: Introductionmentioning
confidence: 99%